El pago directo de alimentos y su incidencia en el desarrollo integral de Niños, Niñas y Adolescentes - Díaz Redrobán, Ángel Ricardo (2022)
The right to food is a fundamental right, without which the fundamental rights of children and adolescents are affected, even putting their lives at risk. This right seeks to provide all the basic needs required by minors to fully develop, given that it not only corresponds to nutritional means but also to other aspects such as education, health, leisure, transportation, etc., Therefore, the importance of this right is recognized, due to its broader and more significant scope within the lives of children and adolescents, being related to the right to life, the right to survival and the right to a dignified life. The importance of the effective fulfillment of this right is not a constant within the existing researches, for this reason, it is important to recognize how this right is made effective through the different forms of providing alimony existing within our regulations, so that the provision of alimony in advance monthly payments is considered as the only one, which has generated a preconceived process within the professional practice of lawyers in child matters, where many times lawyers do not know other forms of providing alimony, besides being an ignorant area for the obligated. Special emphasis is placed on the study of the direct payment of alimony, to recognize whether this regulation allows the right to alimony to fulfill its purpose of guaranteeing the integral development of children and adolescents, by directly supplying the essential needs, both material and immaterial, which are present in the day to day life of this priority group. The study of this problem will serve to deduce in depth the effects of the direct payment of food, within the life of children and adolescents, as well as to understand the importance of their best interest within the right to food. Keywords: children and adolescents, right to alimony, integral development, forms of alimony provision, direct payment of alimony, best interest of child.